The association between lifelong personality and clinical phenotype in the FTD-ALS spectrum - Vinceti, Giulia; Carbone, Chiara; Gallingani, Chiara; Fiondella, Luigi; Salemme, Simone; Zucchi, Elisabetta; Martinelli, Ilaria; Gianferrari, Giulia; Tondelli, Manuela; Mandrioli, Jessica; Chiari, Annalisa; Zamboni, Giovanna (Frontiers in Neuroscience, 2023)
Frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) are two phenotypes of the same neurodegenerative disease, the FTD-ALS spectrum. What determines the development of one rather than the other phenotype is still unknown. Based on the clinical observation that patients' personality seems to differ between the two phenotypes, i.e. ALS patients tend to display kind, prosocial behaviours whereas FTD patients tend to present anti-social behaviours, and that these traits are often reported as pre-existing the disease onset by caregivers, we set up to study experimentally patients' personality in their premorbid life. We first tested for differences between groups, then tested the association between premorbid personality and current functional organization of the brain. Premorbid personality of a cohort of forty patients, 27 FTD and 13 ALS, was explored through the NEO Personality Inventory 3 (NEO-PI-3), which analyses the five main personality factors, completed by the caregiver with reference to patient's personality 20 years before symptoms onset (premorbid). A subgroup of patients underwent a brain MRI including structural and resting-state functional MRI (rsfMRI), analysed with FSL tools. A significant difference between FTD and ALS in premorbid personality emerged in the Openness (133.92 FTD vs 149.84 ALS, p=0.01) and Extraversion (136.55 FTD vs 150.53 ALS, p=0.04) factors. This suggest that ALS had been, in their premorbid life, more open to new experience, more sociable and optimistic than FTD patients. They also showed greater functional connectivity than both FTD and a control group in the Salience resting state network, over and above differences in grey matter atrophy. Finally, there was a positive correlation between premorbid Openness and functional connectivity in the Salience network across all patients, suggesting a possible association between premorbid personality and current functional organization of the brain, irrespective of the degree of atrophy. Our proof-of-concept results suggest that premorbid personality may eventually predispose to the development of one, rather than the other, phenotype in the FTD-ALS spectrum.